To abate, or not to abate? A strategic approach on green production in Cournot and Bertrand duopolies - Domenico Buccella; Luciano Fanti; Luca Gori (Global Labor Organization (GLO), 2020)
This research analyses the firms' strategic choice of adopting an abatement technology in an environment with pollution externalities when the government levies an emission tax to incentivise firms undertaking emission-reducing actions. A set of different Nash equilibria – ranging from dirty to green production – arises in both quantity-setting (Cournot) and price-setting (Bertrand) duopolies depending on the societal awareness towards environmental quality and the relative importance of technological progress in abatement adopted by firms. A synthesis of the main results is the following: if the awareness of the society towards a clean environment is relatively low (resp. high) and the index measuring the relative cost of abatement is relatively high (resp. low), the strategic interaction between two independent, competing and selfish (profit maximising) firms playing the abatement game leads to not to abate [NA] (resp. to abate [A]) as the Pareto efficient outcome: no conflict exists between self-interest and mutual benefit to do not undertake (resp. to undertake) emission-reducing actions. Multiple Nash equilibria or a “green” prisoner's dilemma may also emerge in pure strategies. When the choice of adopting a green technology is a deadlock (anti-prisoner's dilemma), the society is better off as social welfare under A is always larger than under NA because pollution and environmental damage are higher in the latter scenario. These findings suggest that living in a sustainable environment challenges the development of clean technologies through ad hoc R&D and the improvement of public education to achieve an eco-responsible attitude.
Keywords: H23; L1; M5; Q58; 330; “Green” production; Abatement; Emissions tax; Cournot and Bertrand duopolies